2011
DOI: 10.1002/ibd.21623
|View full text |Cite
|
Sign up to set email alerts
|

Mood and nonmood components of perceived stress and exacerbation of Crohnʼs disease

Abstract: The association between perceived stress and exacerbation of CD was fully attributable to the mood components, specifically anxiety and depression. Future interventional studies should evaluate the treatment of anxiety and depression as a strategy for potential prevention of CD exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 20 publications
5
64
0
Order By: Relevance
“…Mittermier et al also described that in CD patients followed for 18 months, there was a significant correlation between Beck Depression Inventory (BDI) scores at baseline and the total number of relapses during of follow-up and that BDI scores at baseline correlated with the time until the first recurrence of the disease [90]. In line with these findings, Câmara et al highlighted that the association between perceived stress and exacerbation of CD was completely attributable to the mood disturbances, specifically anxiety and depression [91].Ananthakrishnan et al showed that depressive symptoms were associated with a 2-fold increase in risk of CD, with both recent and remote (baseline) symptoms playing a role. The effect size of this association was in the same range as those found for current smoking, oral contraceptive use and NSAID use [84].…”
Section: Depression and Inflammatory Bowel Diseasesupporting
confidence: 67%
“…Mittermier et al also described that in CD patients followed for 18 months, there was a significant correlation between Beck Depression Inventory (BDI) scores at baseline and the total number of relapses during of follow-up and that BDI scores at baseline correlated with the time until the first recurrence of the disease [90]. In line with these findings, Câmara et al highlighted that the association between perceived stress and exacerbation of CD was completely attributable to the mood disturbances, specifically anxiety and depression [91].Ananthakrishnan et al showed that depressive symptoms were associated with a 2-fold increase in risk of CD, with both recent and remote (baseline) symptoms playing a role. The effect size of this association was in the same range as those found for current smoking, oral contraceptive use and NSAID use [84].…”
Section: Depression and Inflammatory Bowel Diseasesupporting
confidence: 67%
“…In a prospective study of 101 CD patients with a 1 year follow-up, Bitton et al demonstrated that patients with lower stress and lower scores on avoidance coping were less likely to relapse than those with higher perceived stress 17 . As subsequently demonstrated by Camara et al, the association between perceived stress and exacerbation of CD may be influenced more by mood (depression and anxiety) than non-mood components, making it important to examine whether depression or anxiety are independent risk factors for more severe disease 13 .…”
Section: Discussionmentioning
confidence: 99%
“…We excluded patients who had their first date of diagnosis code for anxiety or depression following the date of first surgery resulting in 2,040 patients (19%) with CD or UC who had either anxiety or depression prior to their surgery. Our primary predictor variable was a composite of the presence of either depression or anxiety prior to surgery for CD or UC 13 . In addition, we analyzed depression and anxiety separately.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors indicate that the same is true for UC [88] . Also in the SIBDCS, anxiety was shown to be a relevant risk factor for disease flares [89] .…”
Section: Environmental Factors Known To Play a Role For Disease Flaresmentioning
confidence: 99%